Warming-induced upward migration of the alpine treeline in the Changbai Mountains, northeast China - Du, Haibo; Liu, Jie; Li, Mai-He; Büntgen, Ulf; Yang, Yue; Wang, Lei; Wu, Zhengfang; He, Hong S (Global change biology, 2018)
Treeline responses to environmental changes describe an important phenomenon in global change research. Often conflicting results and generally too short observations are, however, still challenging our understanding of climate-induced treeline dynamics. Here, we use a state-of-the-art dendroecological approach to reconstruct long-term changes in the position of the alpine treeline in relation to air temperature at two sides in the Changbai Mountains in northeast China. Over the past 160 years, the treeline increased by around 80 m, a process that can be divided into three phases of different rates and drives. The first phase was mainly influenced by vegetation recovery after an eruption of the Tianchi volcano in 1702. The slowly upward shift in the second phase was consistent with the slowly increasing temperature. The last phase coincided with rapid warming since 1985, and shows with 33 m per 1°C, the most intense upward shift. The spatial distribution and age structure of trees beyond the current treeline confirm the latest, warming-induced upward shift. Our results suggest that the alpine treeline will continue to rise, and that the alpine tundra may disappear if temperatures will increase further. This study not only enhances mechanistic understanding of long-term treeline dynamics, but also highlights the effects of rising temperatures on high-elevation vegetation dynamics.
Keywords: Betula ermanii; Trees; forest growth; Temperature; Tundra; Ecosystem; Čína; treeline dynamics; stromy; teplota; dendroecology; China; Changbai Mountains; altitudinal transect; klimatické změny; tundra; climate change; Climate Change; Altitude; ekosystém; nadmořská výška